Sustaining learner engagement and achievement through the study abroad experience - Munyangeyo, Théophile (My University, 2021)
The study abroad, also known as Year Abroad or Period Abroad, has always been and remains a very important part of any language degree programme. Whilst abroad, students are expected to develop language, academic, cultural, intercultural, personal and professional skills; even though some providers’ attention has been leaning on the development of foreign language skills. Self-reported experiences have revealed that after the study abroad, many students fail to use productively acquired skills to cope with demands of the academic complex tasks, including independent major writing projects, various communicative encounters and the development of related soft skills. With an insight into the issues surrounding the curriculum provision, the learning support and the assessment of the study abroad in language programmes, the paper examines and challenges the way many students are prepared and supported to embark on the independent learning journey. The analysis of the findings suggests recommendations for effective learner engagement.
PUBLISHED
Keywords: Study Abroad, reflective learning, self-directed learning, critical thinking, learner engagement, collaborative learning